What just happened - Finch, Charles (Charles B.) (Alfred A. Knopf, 2021)
"A writer and literary critic's diary of the year 2020, beginning with the outbreak of the COVID-19 pandemic and spanning the protests for racial justice and the chaos of the U.S. presidential election"--